Transforming Food Packaging Labels in Food MSMEs through Community Counseling: A Case from Purwodiningratan, Surakarta - Suhardi, Bambang; Dwi Astuti, Rahmaniyah; Aisyah Arifna Putri, Ade; Iftadi, Irwan; Liquiddanu, Eko; Suletra, Wayan (Universitas Ahmad Dahlan, 2025)
Background: Many MSMEs in Indonesia struggle to comply with the packaging label standards from the Indonesian Food and Drug Authority (BPOM). The root of this problem is knowledge gaps among MSME owners about labeling standards. Contribution: This community services program contributes to enhance awareness of BPOM-compliant food packaging among MSMEs through counseling programs. This program differs from previous counseling programs by incorporating digital aids, specifically in redesigning packaging that complies with BPOM standards. Method: Thirty participants attended an interactive discussion and counseling session in Purwodiningratan Village, Surakarta. Using visual aids and digital packaging design examples to show compliance, the session discussed BPOM's standards. Semi-structured interviews and post-session assessments were done to assess influence; descriptive analysis was then used for interpretation. Results: Showed that 80% of the participants engaged actively in conversations, and 70% desired to implement what they learned in the counseling session. Conclusion: The counseling session increased participants' understanding of standard food packaging regulations and shifted their perceptions. Early signs of behavioral change supported the efficiency of participatory counseling in improving MSMEs' compliance with regulations.